Improving Learning Outcomes of Islamic Education Learning Using the Discovery Learning Model at SMP Negeri 4 Mapat Tunggul Selatan - Nurazmi (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve student learning outcomes in Islamic education learning using the discovery learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure student learning outcomes in Islamic education learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the discovery learning model can improve student learning outcomes in Islamic education learning. This can be seen from the increase in the percentage of student activity completion in each cycle with details of the pre-cycle 47.56%, the first cycle 66.47% and in the second cycle increased to 90.57%. Thus, the use of discovery learning model can be used as an alternative to improve student activity in Islamic education learning in Islamic education learning.